Senam Kegel Sebagai Upaya Mengurangi Nyeri Luka Perineum Pada Ibu Nifas di Klinik Bersalin Pera Simalingkar B Medan Tahun 2022 - Hilda Yani Karo Karo; Sri Yunita Perangin angin; Faija Sihombing; Chainny Rhamawan (LPPM Universitas HKBP Nommensen, 2022)
Tears that occur in the perineum during labor or also called perineal lacerations that occur during labor with procedures such as forceps extraction, vacuum extraction, version extraction, kristeller (push on the uterine fundus) and episiotomy. Birth canal tears always provide bleeding in varying amounts. The source of bleeding can be from the perineum, vagina, cervix, and uterine rupture (uterine rupture). Birth canal tears are often found in childbirth assistance by traditional birth attendants. Delivery assistance by health workers with low risk has mild complications so that it can reduce maternal and perinatal mortality (Manuaba, 2013). Morbidity rates due to perineal lacerations include various infections and diseases that accompany pregnancy, childbirth and the puerperium (Friedman, 2012). High risk/complication is a state of deviation from normal, which directly causes morbidity and mortality for both mother and baby. There are several ways that can be used to prevent the occurrence of perineal tears due to normal delivery, including teaching the mother to often do Kegel exercises. Kegel exercises are exercises to strengthen the pelvic floor muscles before delivery, the goal is to strengthen the pelvic floor muscles, help prevent urinary incontinence problems, and can flex the perineal tissue as the baby's birth canal. So that all mothers should be motivated to move the pelvic floor muscles as little and as often as possible, slowly and quickly in the period approaching labor. The Kegel exercise procedure can be remembered and carried out with activities related to the mother's daily activities. Like when you sit in the bathroom after urinating and this is a relaxed position to contract these muscles, and when you want to sleep and under any circumstances. Doing Kegel exercises regularly can help flex the mother's perineal tissue.